A New Approximation For Singular Inverse Sturm-Liouville Problem - Bas, Erdal; Panakhov, Etibar (Chiang Mai Univ, Fac Science, 2012)
In this paper, we study that inverse Sturm-Liouville problem having singularity of type q(x) = delta/x(p) + q(0)(x) at zero point. We prove that the difference between two potential functions q(x) and (q) over tilde (x) becomes sufficiently small whenever the spectral datas {lambda(n), alpha(n)}(n=0)(infinity) and {(lambda) over tilde (n), (alpha) over tilde (n)}(n=0)(infinity) for (q) over tilde (x) and -4 (x) respectively are chosen sufficiently close to each other.
Keywords: spectrum; singular Sturm-Liouville operator; inverse problem; normalized constants